PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - Muhammad Kadir; Muhammad Syarif; Nasrul Nasrul (Pascasarjana Universitas Halu Oleo, 2018)
This study aims to examine and analyze empirically the influence of competence and work discipline on the performance of employees at the Muna Regency Forest Service. This research is explanatory which intends to explain the position of the variables studied and the relationship and influence between one variable and another variable.The results of the study show that: (1) Competence and work discipline have a positive and significant effect on the performance of employees in the Forest Service Office of Muna Regency, Southeast Sulawesi Province. (2) Competence has a positive and significant effect on the performance of employees in the Forest Service Office of Muna Regency, Southeast Sulawesi Province. (3) Work discipline has a positive and significant effect on the performance of employees in the Forest Service Office of Muna Regency, Southeast Sulawesi Province. Keywords: competence, work discipline and employee performance